Effects of two instrument-generation changes on adenoma detection rate during screening colonoscopy: results from a prospective randomized comparative study - Zimmermann-Fraedrich, Katharina; Groth, Stefan; Sehner, Susanne; Schubert, Stefan; Aschenbeck, Jens; Mayr, Michael; Aminalai, Alireza; Schröder, Andreas; Bruhn, Jens-Peter; Bläker, Michael; Rösch, Thomas; Schachschal, Guido (Endoscopy, 2018)
Background Previous studies have shown that multiple colonoscope features have to be changed before an improvement in adenoma detection rate (ADR) becomes obvious, such as with changing from one instrument generation to the next but one. We wanted to evaluate whether such an effect can also be observed in a private-practice screening setting.Methods In a randomized study, we compared the latest generation colonoscopes from one company (Olympus Exera III, 190) with the next to last one (Olympus 165), including only patients presenting for screening colonoscopy. The primary outcome was ADR achieved with 190 colonoscopes (190-C) in comparison with 165 colonoscopes (165-C). Results 1221 patients (46.1 % men; mean age 62.2 years, standard deviation 6.6) were included (599 screened with the Olympus Exera III, 190). The ADR difference in favor of the 190-C instrument (32 % [95 % confidence interval (CI) 26 % to 39 %] vs. 28 % [95 %CI 22 % to 34 %] in the 165-C group) failed to reach statistical significance (P = 0.10); only the rate of small (< 5 mm) adenomas was significantly increased at 22.5 % (95 %CI 19 % to 26 %) vs. 15.6 % (95 %CI 13 % to 18 %; P = 0.002). Furthermore, significantly more adenomas were found in the 190-C group, with an adenoma rate (all adenomas/all patients) of 0.57 (95 %CI 0.53 to 0.61) vs. 0.47 (95 %CI 0.43 to 0.51; P < 0.001). Conclusions This randomized comparative trial in a private-practice screening setting only partially confirmed the results of prior studies that, with multiple imaging improvements achieved over two instrument generations, an increase in overall adenoma number becomes measurable.